A Bibliometric Analysis of Financial Inclusion and Women Empowerment (1997-2021) - Omika Bhalla Saluja (Journal of Informatics Education and Research, 2025)
The study presents a comprehensive bibliometric and systematic review of the literature on financial inclusion (FI) and women's empowerment (WE) from 1997 to 2021. 751 records were initially identified using scope of database and were screened through PRISMA guidelines. Ultimately, 37 key studies were selected for thematic analysis. Bibliometric mapping using VOSviewer helped in discovering leading contributors, prevailing research clusters and thematic trends in psychological, socioeconomic, institutional, digital and sustainability dimensions. Our findings highlight critical gaps including limited comparative research on marginalised women and regional disparity in FI research. This work contributes an interdisciplinary synthesis and offers directions for future Research and policy formulation to increase women's economic participation globally.